Out-of-equilibrium thermodynamics and non-thermal heat engines - Cherubim, Cleverson Francisco (2020)
Quantum thermodynamics (QT) is an emerging field of research that aims to investigate how the laws of thermodynamics and quantum mechanics merge together in small quantum systems. With advances at the necessary technology to control and measure those small physical systems this field has acquired even more importance, not only in the sense that it can be tested, which is a good thing for basic research, but that new applications could be implemented at these scales, so a better comprehension of the limitations imposed by quantum thermodynamics turns out to be of crucial importance for these goals, which forces theoreticians to produce experimentally relevant versions of these new concepts. Another important aspect present at those systems is that part of them work in a regime where its constituents are described by non-thermal states, and in particular non-thermal steady states, which brings to light a different thermodynamic description, usually called steady-state thermodynamics, therefore one of the goals that we are willing to achieve with this thesis is to give an introduction to QT of systems out-of-equilibrium. One of the related subtopics that physicists deal with in QT and the one that we will be focusing on this work are the use of non-thermal stationary states to build heat engines in the quantum domain, and the analyses of the features that this new regime could possibly allow, like the use of quantum resources as a way to overcome classical limitations imposed on its performance, like to attain efficiencies higher than Carnots or operate in certain regimes unattainable using only classical resources. Therefore, in order to clarify the underlying physics of those systems in a non-thermal regime, any experimentally well suited content is more than welcome. So keeping that in mind we devised an experimentally relevant thermodynamic cycle for a transmon qubit WS interacting with a non-thermal environment composed by two subsystems, an externally excited cavity and a classical heat bath with temperature T. The WS undergoes a non-conventional cycle (different from Otto, Carnot, etc.) through a succession of non-thermal stationary states obtained by slowly varying its bare frequency and the amplitude of the field applied on the cavity. The efficiency of this engine obtains a maximum value up to 47% in the regime of operation used. We also wanted to look for the role played by the different types of coherences, present at the WS, on the behavior of the engine and its efficiency. By different types of coherence we mean the so called modes of coherence, whose definition is based on how they respond to symmetry transformations. We did that for the trivial case of the qubit, that only contains the modes 1 and -1, and that has shown to be extremely important for the efficiency of the machine. The same procedure was repeated for a 3-level system WS. The modes 1 and -1 was again very important, not only to the absolute value of the engines efficiency but to the regime of operation of the machine. The additional modes, 2 and -2, had a negative impact on the efficiency, reducing its absolute value. This result appears to show some evidences that quantumness wont necessarily bring improvements to the operation of those machines.